Humic Acid Extracts Leading to the Photochemical Bromination of Phenol in Aqueous Bromide Solutions: Influences of Aromatic Components, Polarity and Photochemical Activity - Liu, Hui (Molecules, 2021)
Dissolved organic matter (DOM) is considered to play an important role in the abiotic transformation of organobromine compounds in marine environment, for it produces reactive intermediates photochemically and is recognized as a significant source of reactive halogen species in seawater. However, due to the complex composition of DOM, the relationship between the natural properties of DOM and its ability to produce organobromine compounds is less understood. Here, humic acid (HA) was extracted and fractionated based on the polarity and hydrophobicity using silica gel, and the influences of different fractions (F(A), F(B) and F(C)) on the photochemical bromination of phenol was investigated. The structural properties of HA fractions were characterized by UV-vis absorption, Fourier transform infrared spectroscopy and fluorescence spectroscopy, and the photochemical reactivity of HA fractions was assessed by probing triplet dissolved organic matter ((3)DOM*), singlet oxygen ((1)O(2)) and hydroxyl radical ((•)OH). The influences of HA fractions on the photo-bromination of phenol were investigated in aqueous bromide solutions under simulated solar light irradiation. F(A) and F(B) with more aromatic and polar contents enhanced the photo-bromination of phenol more than the weaker polar and aromatic F(C). This could be attributed to the different composition and chemical properties of the three HAs’ fractions and their production ability of (•)OH and (3)DOM*. Separating and investigating the components with different chemical properties in DOM is of great significance for the assessment of their environmental impacts on the geochemical cycle of organic halogen.